Testate amoebae (thecamoebian) based reconstruction of Lake Simcoe fringe wetland paleoenvironments - O'Connor, Sheri D. (2014)
Lake Simcoe, Ontario, Canada, a large southern Ontario glacial lake, has been affected by multiple environmental stressors throughout its history. This study uses testate amoebae paleodistribution to reconstruct the environmental conditions of Lake Simcoe's fringe wetlands before and during the Anthropocene. Testate amoebae are unicellular shelled protists that inhabit almost every environment in the world from sandy marine beaches to all freshwater and terrestrial habitats. Their rapid asexual reproduction makes testate amoebae sensitive indicators of short-lived environmental change. Paleolimnological and paleoecological investigations using testate amoebae have been used to describe hydrology, pH, trophic status, land use, climate change, forest fires, oxygen concentrations, metal contamination and other variables. Using compound microscopy techniques, testate amoebae assemblages were identified and tabulated from processed sedimentary cores extracted from fringe wetlands in Lake Simcoe and Tub Lake, with the latter lake used as a reference to assess anthropogenic impact during the Anthropocene. One core, taken from the outlet area of Lake Simcoe, was used to reconstruct the past variability of the paleoenvironment while all four cores were used to reconstruct Anthropocene paleoenvironments. Prior to European settlement three distinct testate amoebae communities inhabited the Victoria Point wetland area based on hydrologic variability: an arctic-like, oligotrophic testate amoebae community dominated by alkaline, lacustrine species; a CaCo3-based community dominated by mesotrophic calcipiles; and an "early fringe wetland community" dominated by aquatic and soil-based species. The anthropogenic activities of the last ~200 years lead to a rapid paludification of the shoreline in all Lake Simcoe wetland locations. Anthropogenic activities have also produced a constant state of disturbance along the shoreline where the mean rate of change in the testate amoebae community since ~AD 1300 (0.46) is greater than the rate of change in the preceding record (0.40). Some of this change is also attributable to recent climate change particularly in the winter and spring, and possibly to the introduction of the Zebra mussel in the mid 1990s. While similarities in the response of testate amoebae assemblages across wetlands do exist, this study has also found that local activities have affected testate amoebae assemblage paleodistributions, species richness and diversity.